Reestructuración técnico administrativa de la planta de producción de la empresa Guala Closures de Colombia ltda. (2018)
In this Project is made the “technical and administrative restructuring of production factory of Guala Closures de Colombia Ltda.” First of all, the project starts with a general diagnosis, which considers internal and external factors, using tools such as PESTAL and DOFA. From this, the weaknesses, strengths, opportunities and threats of the company are identified. Subsequently, a technical study is carried out to identify the current issues of the company, so that generating suggestions for improvements, using tools such as time studies, work methods and capacity analysis. Besides, the administrative area is analyzed in which the strategic planning, the organizational structure is evaluated and also a salary study is carried out for each position of the Company.